THBS1/CD47 Modulates the Interaction of γ-Catenin With E-Cadherin and Participates in Epithelial–Mesenchymal Transformation in Lipid Nephrotoxicity - Gao, Li; Yang, Ting-ting; Zhang, Jun-sheng; Liu, Hong-xia; Cai, Dong-cheng; Wang, Lin-tao; Wang, Jing; Li, Xin-wei; Gao, Kun; Zhang, Su-ya; Cao, Yu-jia; Ji, Xiao-xia; et al. (Frontiers in Cell and Developmental Biology, 2021)
Hyperlipidemia, an important risk factor for cardiovascular and end-stage renal diseases, often aggravates renal injury and compromises kidney function. Here, histological analysis of human kidney samples revealed that high lipid levels induced the development of renal fibrosis. To elucidate the mechanism underlying lipid nephrotoxicity, we used two types of mouse models (Apoe−/− and C57BL/6 mice fed a 45% and 60% high-fat diet, respectively). Histological analysis of kidney tissues revealed high-lipid‒induced renal fibrosis and inflammation; this was confirmed by examining fibrotic and inflammatory marker expression using western blotting and real-time polymerase chain reaction. Oxidized low-density lipoprotein (OX-LDL) significantly induced the fibrotic response in HK-2 tubular epithelial cells. RNA-sequencing and Gene Ontology analysis of differentially expressed mRNAs in OX-LDL-treated HK-2 tubular epithelial cells and real-time PCR validation in Apoe−/− mice showed that the expression of thrombospondin-1 (THBS1) in the high-fat group was significantly higher than that of the other top known genes, along with significant overexpression of its receptor CD47. THBS1 knockdown cells verified its relation to OX-LDL-induced fibrosis and inflammation. Liquid chromatography tandem mass spectrometry and STRING functional protein association network analyses predicted that CD47/thrombospondin-1 modulated the interaction between γ-catenin and E-cadherin, and was involved in epithelial-mesenchymal transition, which was supported by immunoprecipitation and immunohistochemistry. CD47 downregulation following transfection with small-hairpin RNA in OX-LDL-treated tubular epithelial cells, and treatment with anti-CD47 antibody restored the expression of E-cadherin and attenuated renal injury, fibrosis, and inflammatory response in OX-LDL-treated cells and in type 2 diabetes mellitus. These findings indicate that CD47 may serve as a potential therapeutic target in long-term lipid-induced kidney injury.